Effect of mild moxibustion in improving the quality of life of patients with diabetic peripheral neuropathy - Dou-Dou Li; Yu-Hua Zhu; Ting-Li You; Yun-Xia Ge; Xiao-Rong Liu; Xiao Sun (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of this study is to investigate the effect of mild moxibustion on quality of life of patients with type 2 diabetic peripheral neuropathy (DPN). Materials and Methods: Fifty-five patients with type 2 DPN from October 2018 to July 2019 were recruited in the present study and randomly divided into two groups: 27 cases in the control group and 28 cases in the intervention group. The control group received routine treatment of hypoglycemic, hypotensive, mecobalamin nutritional nerve, while the intervention group received mild moxibustion on the basis of the control group. The course of treatment for both groups was 10 weeks. The quality of life of the two groups was assessed using short form-36 health survey and compared with t-test at 0.05 significance level. Results: The total score of the short form-36 in the intervention group was higher than the control group (P < 0.05); the scores of bodily pain, physical functioning (PF), general health (GH), and mental health dimensions in the intervention group increased significantly compared with the control group (P < 0.05); the scores of role physical, social functioning (SF), vitality, and role-emotional (RE) dimensions showed no between-group difference (P > 0.05). Conclusion: Mild moxibustion can effectively improve the quality of life of patients with type 2 DPN, relieve patient pain symptoms, and improve PF and GH.